2015
DOI: 10.1364/ol.40.000363
|View full text |Cite
|
Sign up to set email alerts
|

Design and realization of flexible very large mode area pixelated Bragg fibers

Abstract: A new Pixelated Bragg Fiber design showing improved optical performances in terms of single-mode behavior and effective area is presented. The cladding is made of 3 rings of cylindrical high refractive index rods (pixels) in which some pixels are removed to act as a modal sieve for an improved rejection of Higher Order Modes (HOMs). Two half-wave-stack conditions are used to increase the confinement losses of the 3 first HOMs: LP11 and LP02-LP21 guided core modes. The realized fiber exhibits a core diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The ratio between this diameter and the distance between two adjacent inclusions (Λ) is 0.53. This d/Λ value has been dictated mainly by manufacturing constraints: smaller values (as 0.36 in reference [27]) would lead to fewer resonators and thinner tubes for the low index ring while larger values (as 0.79 in reference [21]) would lead to a very large number of resonators to be stacked into a very small gap. Parametric study of the geometry of the heterostructuration of the two rings was done, starting from the study of a one-ring PiBF (diameter of the first high index ring about 116 µm, so this ring is composed of 16 rods) and then moving to a two-ring PiBF (diameter of second high index ring about 216.6 µm, so the second high-index ring is made of 30 rods) in order to insure robust single-mode behavior.…”
Section: Numerical Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio between this diameter and the distance between two adjacent inclusions (Λ) is 0.53. This d/Λ value has been dictated mainly by manufacturing constraints: smaller values (as 0.36 in reference [27]) would lead to fewer resonators and thinner tubes for the low index ring while larger values (as 0.79 in reference [21]) would lead to a very large number of resonators to be stacked into a very small gap. Parametric study of the geometry of the heterostructuration of the two rings was done, starting from the study of a one-ring PiBF (diameter of the first high index ring about 116 µm, so this ring is composed of 16 rods) and then moving to a two-ring PiBF (diameter of second high index ring about 216.6 µm, so the second high-index ring is made of 30 rods) in order to insure robust single-mode behavior.…”
Section: Numerical Studymentioning
confidence: 99%
“…PiBF is good candidate for the realization of such single-mode fibers because the use of the appropriate Half Wave Stack (HWS) condition applied to low index ring helps to reject Higher Order Modes (HOM) and make the fiber single-mode [26]. Moreover, high-index rings were heterostructured by replacing some high-index rods by pure silica rods so as to enhance HOM leakage [27]. By combining these two different concepts, we have recently showed that pixelated Bragg fiber can be designed to obtain single-mode guidance and very low attenuation (below 25 dB/km between 1200 nm and 1500 nm) with core diameter as large as 48.5 µm [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation